2019
DOI: 10.2903/j.efsa.2019.5594
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Yarrowia lipolytica yeast biomass as a novel food pursuant to Regulation (EU) 2015/2283

Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver a scientific opinion on Yarrowia lipolytica yeast biomass as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The NF is the dried and heat-killed biomass of Yarrowia lipolytica, a yeast species that is widespread in nature and which can be found in the environment as well as in foods. The production process is sufficiently described and does not raise safety concerns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…In its opinion on the safety of Y. lipolytica yeast biomass, the Panel concluded that taking into account the composition and the proposed conditions of use, the consumption of Y. lipolytica yeast biomass is not nutritionally disadvantageous (EFSA NDA Panel, 2019). This conclusion was based on the nutritional analysis of Y. lipolytica biomass (which comprised information on the protein content, amino acid composition, carbohydrates, fibre, fatty acids, vitamins and minerals) and the proposed conditions of use (i.e.…”
Section: Nutritional Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In its opinion on the safety of Y. lipolytica yeast biomass, the Panel concluded that taking into account the composition and the proposed conditions of use, the consumption of Y. lipolytica yeast biomass is not nutritionally disadvantageous (EFSA NDA Panel, 2019). This conclusion was based on the nutritional analysis of Y. lipolytica biomass (which comprised information on the protein content, amino acid composition, carbohydrates, fibre, fatty acids, vitamins and minerals) and the proposed conditions of use (i.e.…”
Section: Nutritional Informationmentioning
confidence: 99%
“…This conclusion was based on the nutritional analysis of Y. lipolytica biomass (which comprised information on the protein content, amino acid composition, carbohydrates, fibre, fatty acids, vitamins and minerals) and the proposed conditions of use (i.e. up to 3 g/day for children from 3 to 9 years of age and up to 6 g/day thereafter) (EFSA NDA Panel, 2019).…”
Section: Nutritional Informationmentioning
confidence: 99%
“…The EFSA NDA Panel has previously favourably assessed the safety of Y. lipolytica yeast biomass as a novel food (EFSA NDA Panel, ).…”
Section: Assessmentmentioning
confidence: 99%
“…As noted in the previous safety assessment of Y. lipolytica (EFSA NDA Panel, ), the Panel reiterates that in order to monitor the efficacy of the heat treatment and to guarantee that there are no viable Y. lipolytica cells remaining in the dried biomass, testing for the presence of viable yeast cells has to be carried out immediately after the heat treatment (see also Specifications, Table ).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation